Growth and reproductive performance of small ruminants under integrated livestock oil palm production system - Abdullah, Ramli; Mukherjee, T.K.; Baba, A.S.H.; Azillah, A. (1998)
The effects of supplementation with mixed fodder or concentrate were investigated on the performance of a) growth of male lambs;md kids grazing extensively under oil palm trees and b) reproduction of ewes and goats stall-fed with native herbage. Supplemented kids and lambs had higher average daily weight gain than controls but the effect was only significant for those which received concentrate (p < 0.05). Final body weight was only significantly different from controls for lambs supplemented with concentrate (p < 0.05). The ages at puberty, first mating, first conception and first kidding of supplemented goats were about 110 days earlier than those for controls (p < 0.05 or better). Supplemented goats had first mating and conceived at lower body weights (p < 0.01) than those in control groups. Different feeding regimes had no effects (p > 0.05) on the reproductive performance of ewes apart fi om highest body weight of first lambing in animals supplemented with concentrate (p < 0.05). Native herbage available under oil palm trees of 5 years old was sufficient for growth and reproduction of sheep and goats. Concentrate was better than mixed fodder as supplement for enhancing the reproductive performance of goats but both appeared to have limited effects on the performance of reproduction in ewes and growth in male kids.